Analysis of the Integration of Halal Principles and Sustainable Beauty Principles in Cosmetics: Conceptual and Empirical Review - Junaidin Junaidin; Riki Riki; Arman Rusman; Harra Ismi Farah; Maria Almeida; Hanggara Arifian; M. Arifuddin Arifuddin; Hifdzur Rashif Rija'i; Erwin Samsul; Rolan Rusli; Arsyik Ibrahim; Herman Herman; Islamudin Ahmad; Baso Didik Hikmawan; Lizma Febrina (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The growing convergence of halal and sustainable beauty attributes has created a need to understand how consumers translate these product perceptions into purchase intention. This study examines the effects of Halal Product Perception and Sustainable Beauty Perception on Purchase Intention through Perceived Value and Consumer Trust among cosmetic consumers in Indonesia. A quantitative explanatory design was employed using purposive sampling, involving 300 respondents who had experience using cosmetics and had encountered information about halal cosmetics and/or sustainable beauty. Data were collected through a structured questionnaire comprising 29 reflective indicators measured on a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings show that Halal Product Perception and Sustainable Beauty Perception positively influence Perceived Value and Consumer Trust, while both mediators positively influence Purchase Intention. Halal Product Perception also has a significant direct effect on Purchase Intention, whereas Sustainable Beauty Perception does not. Mediation analysis reveals that Halal Product Perception influences Purchase Intention through complementary mediation via Perceived Value and Consumer Trust, while Sustainable Beauty Perception operates through indirect-only mediation. These findings indicate that halal attributes can function as both direct purchasing considerations and sources of value and trust, whereas sustainability perceptions require value and credibility formation before translating into purchase intention. The study contributes to an integrated understanding of halal-sustainable cosmetic consumption and offers practical implications for developing credible product attributes and transparent communication strategies.